Effectiveness of unilateral sequential video-assisted sympathetic chain blockage for primary palmar hyperidrosis in children and adolescents - Adorisio, Ottavio; Davoli, Enrico; Ceriati, Emanuela; Battaglia, Sonia; Camanni, Daniela; De Peppo, Francesco (Frontiers in Pediatrics, 2022)
Introduction Primary palmar hyperhidrosis (PPH) is a severely debilitating condition that can affect patients of any age. Thoracoscopic sympathectomy provides a definitive treatment for PPH. Aim of this study is to investigate the effectiveness of unilateral sequential video-assisted thoracic sympathetic chain clamping (VATSCC) by clips application in pediatric population. Methods From August 2017 to September 2021, 58 patients (male:female ratio 32:26), mean age 16.5 years (range 14-19), affected PPH underwent unilateral sequential VATSCC by clips application, starting on the dominant hand. The contralateral side was operated 2 months after. Resolution of symptoms, complications, recurrence rate, onset and duration of compensatory hyperhidrosis were analyzed. Results The surgical procedure was done in the semi-sitting position, under general anesthesia with OT intubation. Mean operation time was 23±6 minutes (range 12-45). Two 5 mm ports were inserted at the level of the middle axillary line in the second e fourth intercostal space respectively. The sympathetic chain was identified, and two clips were applied at the level of the third and fourth rib. No chest tube was used. All patients except one (transient pneumothorax) were discharged on the first post-op day. No immediate or late complications have been recorded. Mean follow-up was 32 months (range 6-41). All patients except one (2.1%), affected by Raynaud’s disease, showed a complete resolution of the symptom. Seven patients (15%) developed transient moderate compensative hyperhidrosis (CH) that spontaneously disappeared a few weeks after. Conclusions Unilateral sequential thoracoscopic sympathetic chain clamping for pediatric patients with PPH is safe and very effective in reducing CH, with a very low complication rate and high post-operative quality of life.